JUAL BELI ONLINE PERSPEKTIF HUKUM ISLAM - Agus Riyanto; Ria Andrianie (Economic Faculty, University of Widya Gama Mahakam Samarinda, 2024)
The development of information and telecommunications technology is growing rapidly from time to time so that people's lifestyles also go hand in hand with increasingly sophisticated technological developments causing people to follow a modern lifestyle, where people can carry out buying and selling transactions that used to often occur in markets and supermarkets and up to Currently buying and selling has appeared in the form of online buying and selling transactions using mobile phones and the help of the internet network. This study aims to examine the review of Islamic law on buying and selling online. The approach used in this study is a qualitative approach, namely an approach using data in the form of written sentences, events, knowledge or study projects that are descriptive in nature. This research is classified as library research, which examines the subject matter through literature or references that are related and relevant to the title of this research.